Mitochondrial membrane assembly of TMEM70 protein - Kratochvílová, Hana; Hejzlarová, Kateřina; Vrbacký, Marek; Mráček, Tomáš; Karbanová, Vendula; Tesařová, Markéta; Gombitová, Adriána; Cmarko, Dušan; Wittig, Ilka; Zeman, Jiří; Houštěk, Josef (Mitochondrion, 2014)
Dysfunction of TMEM70 disrupts the biogenesis of ATP synthase and represents the frequent cause of autosomal recessive encephalocardiomyopathy. We used tagged forms of TMEM70 and demonstrated that it has a hairpin structure with the N- and C-termini oriented towards the mitochondrial matrix. On BN-PAGE TMEM70 was detected in multiple forms including dimers and displayed partial overlap with assembled ATP synthase. Immunoprecipitation studies confirmed mutual interactions between TMEM70 molecules but, together with immunogold electron microscopy, not direct interaction with ATP synthase subunits. This indicates that the biological function of TMEM70 in the ATP synthase biogenesis may be mediated through interaction with other protein(s).
Keywords: mitochondriální proteiny; Cell Line; Membrane Proteins; Mitochondrial Membranes; Protein Multimerization; mitochondriální protonové ATPasy; Mitochondrial Proton-Translocating ATPases; lidé; imunoprecipitace; multimerizace proteinu; buněčné linie; Microscopy, Immunoelectron; Immunoprecipitation; Mitochondrial Proteins; membránové proteiny; mitochondriální membrány; imunoelektronová mikroskopie; Humans